Antioxidant and anticholinesterase properties of Echinometra mathaei and Ophiocoma erinaceus venoms from the Persian Gulf - Dehghani, Hamideh; Rashedinia, Marzieh; Mohebbi, Gholamhossein; Vazirizadeh, Amir; Baghban, Neda (Frontiers in Chemistry, 2024)
The Persian Gulf is home to a diverse range of marine life, including various species of fish, crustaceans, mollusks, and echinoderms. This study investigates the potential therapeutic properties of venoms from echinoderms in the Persian Gulf, specifically their ability to inhibit cholinesterases (Acetylcholinesterase and butyrylcholinesterase) and act as antioxidants. Four venoms from two echinoderm species, including the spine, gonad, and coelomic fluids of sea urchins, as well as brittle star venoms, were analyzed using various methods, including LD50 determination, protein analysis, antioxidant assays, GC-MS for secondary metabolite identification, and molecular docking simulations. The study's results revealed the LD50 of the samples as follows: 2.231 ± 0.09, 1.03 ± 0.05, 1.12 ± 0.13, and 6.04 ± 0.13 mg/ml, respectively. Additionally, the protein levels were 44.037 ± 0.002, 74.223 ± 0.025, 469.97 ± 0.02, and 104.407 ± 0.025 μg/ml, respectively. SDS-PAGE and total protein studies indicated that at least part of the venom was proteinaceous. Furthermore, the study found that the brittle star samples exhibited significantly higher antioxidant activity compared to other samples, including the standard ascorbic acid, at all tested concentrations. GC-MS analysis identified 12, 23, 21, and 25 compounds in the samples, respectively. These compounds had distinct chemical and bioactive structures, including alkaloids, terpenes, and steroids. The results showed that 2 This is a provisional file, not the final typeset article these venoms displayed strong cholinesterase inhibitory and antioxidant activities, likely attributed to their protein content and the presence of alkaloids, terpenes, and steroids. Notably, the alkaloid compound C7 was identified as a promising candidate for further research in Alzheimer's disease therapy. In conclusion, echinoderms in the Persian Gulf may hold significant potential for discovering novel therapeutic agents.